2018
DOI: 10.1155/2018/2789691
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Origin in the Zagreb Aquifer System

Abstract: Nitrates are among the most common groundwater contaminants worldwide, and the same situation is present within the Zagreb aquifer. The Zagreb aquifer presents the only source of potable water for inhabitants of the City of Zagreb and part of Zagreb County. Isotopic composition of water (δ2H and δ18O) and nitrates (δ15N and δ18O), groundwater chemistry, and molar ratios, in combination with correlation and multivariate statistical methods, have been used for the estimation of nitrate origin. Nitrate stable iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…For example, the ranges of isotopic compositions of nitrate suggested that the major sources of nitrate in the large Changjiang (Yangtze) River come from modified fertilizer and urban sewage effluent [21]. Wastewater was found to be the main source of nitrate contamination in urban areas [22]. The nitrate input from rainfall to groundwater is often neglected, but nitrification is generally regarded as a prerequisite for nitrate leaching [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ranges of isotopic compositions of nitrate suggested that the major sources of nitrate in the large Changjiang (Yangtze) River come from modified fertilizer and urban sewage effluent [21]. Wastewater was found to be the main source of nitrate contamination in urban areas [22]. The nitrate input from rainfall to groundwater is often neglected, but nitrification is generally regarded as a prerequisite for nitrate leaching [23].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of elevated nitrate concentrations in the Zagreb aquifer have been confirmed through recent research (Kovač, Cvetković, & Parlov, 2017;Kovač, Nakić, & Pavlić, 2017). It has been shown that nitrate trends are declining in most parts of the Zagreb aquifer (Kovač, Nakić, Špoljarić, Stanek, & Bačani, 2018), and that nitrate origin is mostly organic, generally associated with wastewater leaching from permeable sewage and septic tanks (Kovač, Nakić, Barešić, & Parlov, 2018). Furthermore, nitrate stable isotopes composition has shown that the denitrification process is negligible in most parts of the Zagreb aquifer.…”
Section: Introductionmentioning
confidence: 80%
“…Data used to create the risk of nitrate contamination map in the area of the Zagreb aquifer were adjusted to the area of approximately 300 km 2 . Data were collected from previous research (Kovač, 2017;Kovač, Nakić, Barešić, et al, 2018;Ružičić, 2013), official documents of the Republic of Croatia and various registers of the Republic of Croatia: Hydrogeological map of the Republic of Croatia M 1:300,000 (Biondić, Brkić, Biondić, & Singer, 1996), Outlines of Water Management of the Republic of Croatiasection Groundwater (Biondić & Brkić, 2001), CORINE Land Cover 2012 (Croatian Environmental and Nature Agency, 2018a), WFS layer of The Register of industrial plants in which the presence of dangerous substances was established (Croatian Environmental and Nature Agency, 2018b) and Farm register used in Kovač (2017). Higher concentrations of nitrates in groundwater are thought to be a consequence of multiple different sources, as well as the aquifer properties.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations